2003
DOI: 10.1002/jssc.200301527
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the retention behaviour of steroids with calixarene‐based stationary phases by modern NMR spectroscopy

Abstract: Investigation of the retention behaviour of steroids with calixarene-based stationary phases by modern NMR spectroscopy A separation of four structurally similar steroids was performed on two calix[8]arene based stationary phases. It was observed that two of the steroids had a reversed retention order when the columns were changed. This implies that two different retention mechanisms are taking place when the analytes are separated. In order to evaluate the mechanism responsible for the reversal of the retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…As an example, the transferred NOESY study of the interactions between various steroids and calix [8]arene-based stationary phases is mentioned. 51 Similar studies related to chiral interactions are shown in the last section of this review.…”
Section: ·5 Nmr Spectroscopysupporting
confidence: 73%
“…As an example, the transferred NOESY study of the interactions between various steroids and calix [8]arene-based stationary phases is mentioned. 51 Similar studies related to chiral interactions are shown in the last section of this review.…”
Section: ·5 Nmr Spectroscopysupporting
confidence: 73%
“…We assume that specific interactions with the cavities of the calixarenes and resorcinarenes are responsible for these phenomenon. HR-MAS-NMR studies confirm a stronger interaction of chlormadinone acetate with AIII in comparison to BIII, which was due to better -interactions [38]. Thus, phases with supramolecular selectors are able to detect differences of the analytes with similar lipophilicity.…”
Section: Separation Of Thioxanthenes and Steroidsmentioning
confidence: 84%
“…Several techniques such as UV , NMR , electrochemical , chromatographic , and capillary electrophoretic techniques were used to ensure that calixarenes make inclusion complexes with different analytes. Calixarenes have several applications in anion receptors , CE as additives , polymeric materials , GC , and HPLC .…”
Section: Introductionmentioning
confidence: 99%